Taxonomy of Bradysia Winnertz (Diptera, Sciaridae) in the Northern Holarctic, with the description of four new species - Heller, Kai; Hippa, Heikki; Vilkamaa, Pekka (European Journal of Taxonomy, 2015)
Four species of Bradysia Winnertz (Diptera, Sciaridae) from the Northern Holarctic are described and illustrated for the first time: Bradysia bigeminata sp. nov. (Finland, Canada), B. falciceps, sp. nov. (Finland, Canada), B. oelandica sp. nov. (Sweden) and B. plusiospina sp. nov. (Finland). A few Bradysia species, described previously and now found in Northern Europe, are also redefined and illustrated.